- #1

- 245

- 0

Okay say we know from magnetism.

E = F / q

F = KQq / R^2

Then we can say that.

E = KQq / (R^2 / q)

Then wouldn't we say

E = KQq * q / R^2

E = KQq^2 / R^2

Its just like saying.

5 / (1 / 2) = 5 * 2 / 1 = 10.

Why is it we cancel the q's instead of squaring them, because my textbook does that and ends up with this equation.

E = KQ / R^2

Because the answers are different. Thanks.

E = F / q

F = KQq / R^2

Then we can say that.

E = KQq / (R^2 / q)

Then wouldn't we say

E = KQq * q / R^2

E = KQq^2 / R^2

Its just like saying.

5 / (1 / 2) = 5 * 2 / 1 = 10.

Why is it we cancel the q's instead of squaring them, because my textbook does that and ends up with this equation.

E = KQ / R^2

Because the answers are different. Thanks.

Last edited: